1976
DOI: 10.1111/j.1469-8986.1976.tb03085.x
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Control of Electrodermal Activity in Relation to Imagery and Internal Perception Scores

Abstract: feedback of spontaneous Electro dermal fluctuation in human subjects increased their in frequency of occurrence relative to a non‐contingent feedback control group. The effect was facilitated for subject having high imagery und/or high internal perception as measured by the Suphian Scale of Imagery (SSI) and Sophian Scale of Internal Perception (SSP) respectively. These data suggest the existence of individual differences in self‐control of autonomic responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This possibility has been proposed by Iacono and Lykken (1984), although Gruzelier and Eves (1987) failed to find a difference between instruction to passively ignore tones or inhibit responses to them. While evidence of indirect control on overall reactivity including SCLs has been provided through training in biofeedback and relaxation (Klinge, 1972;Ikeda and Hirai, 1976;Critchley et al, 2002;Nagai et al, 2004a,b), evidence of relatively spontaneous self-control on ORs is still sparse (see Lacroix and Roberts, 1978).…”
Section: Discussionmentioning
confidence: 97%
“…This possibility has been proposed by Iacono and Lykken (1984), although Gruzelier and Eves (1987) failed to find a difference between instruction to passively ignore tones or inhibit responses to them. While evidence of indirect control on overall reactivity including SCLs has been provided through training in biofeedback and relaxation (Klinge, 1972;Ikeda and Hirai, 1976;Critchley et al, 2002;Nagai et al, 2004a,b), evidence of relatively spontaneous self-control on ORs is still sparse (see Lacroix and Roberts, 1978).…”
Section: Discussionmentioning
confidence: 97%
“…In the HR increase condition, differences in the reported characteristic vividness of visual imagery tended to be reflected in the extent of HR increases. Recently, Ikeda & Hirai (1976) have reported indications of a similar relationship between differences in imagery vividness and voluntary increases in the frequency of skin potential responses. However, in their study it is unclear to what extent subjects actually employed imagery in the pursuit of skin potential response control.…”
Section: Discussionmentioning
confidence: 83%
“…(The MIS is highly correlated to presumed effects on planning and teaching criteria.) Ikeda and Hirai (1976) similarly disputed the efficacy of the Sophian scales and reported that individual differences in subjects' self-control of autonomic electrodermal activity affected imagery responses. (Reing, 1970; Reing, Note 1 ).…”
mentioning
confidence: 95%
“…An innovative methodology for individual and group psychotherapy, called clinical eidetics, employing imagery to reveal and resolve conflict areas, has been generated (Ahsen, 1977). The psychophysical effects of imagery mediated by instructional sets on parasympathetic reactions (Ikeda & Hirai, 1976) and heart rate and muscle tension, but not respiration rate (Beiman, 1976), have also been shown. ' In summary, prior investigators have successfully developed and applied different imagery models within the context of word retention, memory, and coding tasks, as well as verbalized thinking and effective behaviors.…”
mentioning
confidence: 97%